Dietary sources and meal distribution of sodium and potassium in a sample of Australian adults. Issue 4 (3rd June 2013) - Margerison, Claire; Riddell, Lynnette J.; Wattanapenpaiboon, Naiyana; Nowson, Caryl A.
Abstract Aim Reducing dietary sodium and increasing dietary potassium are recommended to reduce blood pressure. This study aimed to determine the main foods sources of sodium and potassium. Methods Participants were recruited via advertisements or blood pressure screening sessions. Food sources of sodium and potassium were assessed via 24‐hour dietary records in 299 free‐living Australian adults (141 male, 158 female; age 54.6(9.5)years; BMI 29.4(3.9)kg/m2). Results The mean sodium intake was 118(51)mmol/d (2725(1176)mg/d) and the mean potassium intake was 91(28)mmol/d (3550(1098)mg/d). Breads and cereals provided the majority (38%) of sodium with bread contributing 20%. Vegetable products/dishes contributed most potassium (23%) with potatoes providing 9%. Main meals provided 89% of sodium and 85% of potassium. Lunch and dinner provided similar sodium proportions (34% and 38%, respectively) but more energy was consumed at dinner (26% vs 40%, respectively). Lunch had the highest sodium density of all meals (420 mg/MJ). Conclusion A reduction in the salt content of processed foods, particularly bread, is recommended to decrease sodium intake. This reduction in salt content combined with meal specific education focusing on choosing lower sodium foods at lunch in particular, as well as incorporating more fruits and vegetables, could effectively reduce dietary sodium and increase potassium.